Anisa: artificial intelligence companion for elderly care with empathetic conversations and health management - Karegoudra, Shilpa; Hegde, Pawan; Poojary, Sinchana C.; Shetty, Pranitha P.; Kotian, Sahana M.; Kallianpur, Saanvi; Koti, Veeresha R. (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
This study introduces Anisa, an advanced artificial intelligence (AI) companion designed to enhance elderly care by addressing the multifaceted needs and challenges of older adults. The system integrates the Llama 3.2 model, powered by Groq, to facilitate context-aware dialogues and empathetic interactions. This capability helps alleviate loneliness and provides essential companionship. Agenda.js is used for scheduling and managing reminders, ensuring timely notifications for medications and appointments. Additionally, Twilio enables emergency alerts when distress signals are detected. Anisa promotes physical activity, tracks daily routines, and generates activity reports shared with caregivers and healthcare providers. Expo CLI implements step-tracking and document-sharing features. By integrating these functionalities, Anisa improves the quality of life for seniors, eases caregiver responsibilities, and fosters a safer, more supportive environment.